On nonconvex perturbations of maximal monotone differential inclusions - Bressan, Alberto
The paper is concerned with the evolution inclusionxAx+F(t,x), whereA generates a contractive semigroup andF is a lower semicontinuous multifunction. Constructing a suitable directionally continuous selection fromF, we prove the existence of solutions on a closed domain and the connectedness of the set of trajectories.